Low birth weight and associated factors in rural population of Rajasthan, India - Sangwan, Ramesh Kumar; Huda, Ramesh Kumar; Khetan, Mukti; Gazta, Parul; Kumar, Pankaj; Babu, Bontha V. (Frontiers in Global Women's Health, 2025)
BackgroundLow Birth Weight (LBW) significantly affects childhood survival, with the socio-demographic characteristics (maternal age, child's gender, education, maternal diseases and others) contributing to it. The study aims to identify social determinants contributing to LBW, which can further be useful in developing local interventions to rectify the problem in an Indian rural context.MethodologyThe cross-sectional study was conducted in the Jalore district of Rajasthan, India. A total of 92 delivery cases, including LBW (n = 46) and cases with normal birth weight (n = 46), became part of the research. A pre-tested questionnaire collected information from study participant groups enumerating deliveries from selected Primary Health Centres (PHCs) related to LBW and non-LBW deliveries in a 1:1 ratio.ResultsThe study recorded a total of 1,251 deliveries, of which 63 resulted in the LBW (<2,500 grams), nine were premature, 12 were twin births, and 361 were normal weight deliveries (≥2,500 grams). LBW was prevalent in underprivileged communities within nuclear families, having an average birth weight of 2.12 kilograms. Reduced meal frequency (1–2 times a day) for women is also linked to higher LBW risk.ConclusionMany factors, like complications during pregnancy, awareness of pregnancy planning, and nutritional intake, are associated with the likelihood of LBW occurrences. Many maternal risk factors for LBW are modifiable through early detection by imparting education and awareness to pregnant women in their first trimester. The findings emphasize the significance of targeted interventions and awareness programs to address specific risk factors and improve birth outcomes in rural Indian communities.